Feeling Proud and Being Proud: An Investigation Into the Moral Psychology of Personal Ideals - Fischer, Jeremy Michael (My University, 2012)
I argue that there are two sorts of pride--the emotion of pride and the character trait of pride--and defend descriptive and normative accounts of each sort of pride. The emotion of pride involves an evaluation that one is living in accordance with one's personal ideals; having the character trait of pride is having a firm commitment to living in accordance with one's personal ideals. Thus, the two sorts of pride are conceptual related insofar as they each embody a distinct aspect of the moral psychology of personal ideals: the emotion embodies the evaluative use of personal ideals, whereas the character trait embodies the practical influence of personal ideals. In Chapter 1, I outline and defend a conceptual framework for analyzing emotions that distinguishes between two kinds of considerations that may count in favor of having an emotion. In Chapter 2, I survey the philosophical literature on the emotion of pride and argue that extant accounts of pride are classifiable into three groups: identification accounts, agency accounts, and possession accounts. I argue that each of the three sorts of accounts has significant merits, but that each ultimately fails to provide a satisfactory descriptive account of pride. In Chapter 3, I develop and defend personal ideal-based descriptive and normative accounts of the emotion of pride. In Chapter 4, I provide a relational account of personal ideals that solves two puzzles about pride: the sociality puzzle (to explain how pride can be both a profoundly personal and a deeply social phenomenon) and the hierarchy puzzle (to explain how pride can be implicated in the social dynamics of both hierarchy and solidarity). In Chapter 5, I defend a descriptive and a normative account of the character trait of pride in terms of being firmly committed to living in accordance with one's personal ideals.
Thesis (Ph.D.)--University of Washington, 2012
Keywords: Character; Emotion; Ethics; Personal Ideals; Pride; Philosophy; Philosophy